2005
DOI: 10.1007/s11224-005-2836-7
|View full text |Cite
|
Sign up to set email alerts
|

Complete NMR Elucidation of Two N-Protected Trishomocubane Hydantoins and the Ethyl Ester of the Corresponding Amino Acid

Abstract: In an attempt to resolve a racemic mixture of a trishomocubane hydantoin, the synthesis of a pair of novel diastereomers was obtained by protecting the racemic hydantoin with chlorocarbonic acid-(−)(R)-sec-butyl ester. An achiral i-propyl ester was first used to establish the procedure. The NMR elucidation of both the chiral and achiral N-protected hydantoins is described. Some proton and carbon NMR shifts on the cage are reversed when relative small changes on the protection group are introduced. The chiral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…The racemic hydantoins (3)(4)(5) are synthesized from acetaldehyde, acetone and PCU monoketone [16,17] under normal Bucherer-Bergs [18,19] conditions. Mono-and bis-Boc protection of the hydantoins have not been reported before.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The racemic hydantoins (3)(4)(5) are synthesized from acetaldehyde, acetone and PCU monoketone [16,17] under normal Bucherer-Bergs [18,19] conditions. Mono-and bis-Boc protection of the hydantoins have not been reported before.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In a recent study [4], it was demonstrated that the trishomocubane hydantoin 1 is selectively protected at N-3 . It appears as if competition between N-1 (more steric hindrance but stronger nucleophile) and N-3 (less steric hindrance but less nucleophilic) influence the course of the reaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] The synthesis of the first trishomocubane amino acid (3) was recently reported. 8,9 To understand the function of peptides and proteins in biological processes, knowledge of their molecular structure is an essential prerequisite. Therefore, structural investigations on novel constrained amino acids are relevant areas of study.…”
Section: Introductionmentioning
confidence: 99%